THE DEFINITION OF MAGICAL REALISM IN THE WORKS OF ISABEL ALLENDE, GABRIEL MARQUEZ, AND LAURA ESQUIVEL - Dzhuldyzai Orynbasarovna Kaldybaeva (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides a brief overview of such a literary movement as magical realism. The meaning of the term, the origin and development of the literature of this genre are also considered. The work of three famous authors is considered: Garcia Marquez, Isabel Allende and Laura Esquivel. Magic realism is one of the most unique literary movements of the last century. Although it is most commonly associated with Latin American authors, writers from all over the world have contributed greatly to the development of the genre.